Geographic diversity of human liver cancers mirrors global social inequalities - Cano, Luis; Foucher, Fabien; Musso, Orlando (Frontiers in Oncology, 2025)
Liver cancers show high interindividual and intratumor heterogeneity. Among them, hepatocellular carcinoma (HCCs) represents approximately 90% of liver cancers, followed by intrahepatic cholangiocarcinoma (iCCA; ~10 to 15%), childhood hepatoblastoma, angiosarcoma and hemangioendothelioma (< 1%). More than 80% of HCCs arise in a backdrop of chronic inflammatory liver diseases of diverse etiologies. These underlying liver diseases are major determinants of geographic diversity of HCCs. Across the world, substantial differences in the prevalence of chronic viral hepatitides, alcohol misuse, Metabolic Disfunction-Associated Steatotic Liver Disease (MASLD) and exposure to toxic substances are frequently related to social and economic inequalities. Vulnerable populations are more frequently exposed to infections such as hepatitis B and C viruses that, combined with other risk factors, lead to both vertical and horizontal transmission and, in turn, impact on age and sex-related diversity. In this review, we describe the global landscape of risk factors leading to HCC: MASLD, chronic hepatitis B and C infections, alcohol misuse, exposure to other toxic substances and genetic predispositions. We describe their combined effects on the clinical and epidemiological features of HCCs around the globe. Clinical presentation, incidence and mortality rates of HCCs show therefore great geographic heterogeneity, which is also related to the inequalities in the gross domestic product per capita, the socio-demographic index, the access to health care resources and to the implementation of policies for surveillance and screening of patients at risk. Awareness of the biological and geopolitical sources of HCC diversity will hopefully lead to more efficient international cooperation in the prevention and early management of chronic liver diseases and HCC.